1986
DOI: 10.1093/ajcn/44.6.986
|View full text |Cite
|
Sign up to set email alerts
|

The 1986 McCollum award lecture. Fuel-mediated teratogenesis during early organogenesis: the effects of increased concentrations of glucose, ketones, or somatomedin inhibitor during rat embryo culture

Abstract: Whole rat embryos were explanted at head-fold, late pre-somite stage (day 9.5 of gestation) and cultured in rat sera varyingly supplemented with glucose (3, 6, 9, or 12 mg/mL), D,L sodium beta-hydroxybutyrate (2, 4, 8, or 16 mM), or both (6 mg/mL D-glucose plus 8 mM beta-hydroxybutyrate). During 48 h culture, increasing glucose alone or beta-hydroxybutyrate alone effected growth retardation and faulty neural and extraneural organogenesis in dose-dependent fashion. Synergistic dysmorphogenic effects occurred wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…Altogether these data would support the notion of a multiple origin of the embryonic maldevelopment in diabetic pregnancy (23,48,50,51).…”
Section: Ud Hn Hdsupporting
confidence: 76%
“…Altogether these data would support the notion of a multiple origin of the embryonic maldevelopment in diabetic pregnancy (23,48,50,51).…”
Section: Ud Hn Hdsupporting
confidence: 76%
“…The earliest detection of receptor for somatomedin C has been at day 10 for mouse embryo [37] and for epidermal growth factor receptors at day 12 [38]. The findings that somatomedin inhibitors from diabetic rat serum retarded growth and development in rat [36] and mouse [35] embryos suggest a possible role of somatomedin in early embryonic development. We can not exclude the possibility that decreased activity of somatomedin [34] and increased counterregulatory hormones [33] in insulin-induced hypoglycaemic serum may have been involved as well.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental insults during this developmental window lead to defects in the cardiovascular system, which subsequently affect the development of several embryonic organs. An in vitro whole embryo culture model permits study of this crucial developmental period and has shown that short exposure to hyperglycemia is teratogenic, causing dose dependent growth retardation, neural tube lesions and yolk sac failure (Cockroft and Coppola, 1977;Pinter et al, 1999;Reece et al, 1996;Rashbass and Ellington, 1988;Sadler, 1980a;Sadler, 1980b;Freinkel et al, 1986). Additionally, this model system mimics the morphological and biochemical vascular defects in the embryo and yolk sac observed in vivo (New et al, 1976;Mills et al, 1979;Sadler and Warner, 1984).…”
Section: Introductionmentioning
confidence: 99%